Socjologiczne aspekty kształtowania się pogranicza polsko-niemieckiego po II wojnie światowej - Trosiak, Cezary (Wydział Prawa i Administracji UAM, 1992)
The author presents borderland as a theoretical category, exemplifing his considerations by the findings of pre- and post war Polish sociology. The autor discusses the history of Polish-German borderland over the last 200 years, with special attention paid to contacts between the inhabitants of borderland. He also points to the symptoms of formation of Polish-German borderland along the Odra-Nysa rivers after 1972, and to the existence of a so-called borderland society (including German minority on Western Territories of Poland). Finally, the autor points to varions social, economic and cultural phenomena taking place in the Western Territories and indicates that those issues should become the object of extensive sociological research.
Sociological aspects of formation of Polish-German borderland after the World War ll